Nivolumab-induced contact dermatitis in a patient with advanced lung cancer. (2020) - Sato, Shintaro; Oba, Tomohiro; Ohta, Hiroki; Tsukahara, Yuta; Kida, Gen; Tsumiyama, Emiri; Kusano, Kenji; Nishizawa, Tomotaka; Kawabe, Rie; Yamakawa, Hideaki; Akasaka, Keiichi; Amano, Masako; et al.
Abstract: An 85-year-old man was being treated for advanced squamous cell lung carcinoma with nivolumab as a second-line treatment. From the beginning of the third course, erythema appeared on his trunk and gradually progressed. Around the start of the fifth course, erythema spread to the proximal part of all limbs in addition to the trunk and was accompanied by a strong itching sensation. He was diagnosed as having contact dermatitis by a dermatologist because his rash was observed only where the moisture-absorbing fiber material of his underwear made contact with the skin surface. After suspending treatment of nivolumab, changing his underwear to a cotton material, and using moisturizers and steroid ointments, his rash disappeared in about a month and the size of his lung tumors remained reduced. The patient developed contact dermatitis despite the use of similar underwear without any skin problems for several years. We speculated that nivolumab-induced T-cell activation may have occurred in his skin, making him more likely to develop contact dermatitis, whose onset is thought to involve T-cell activation. No cases of contact dermatitis have been reported previously although the frequency of eruption as an immune-related adverse event is relatively high. When using immune checkpoint inhibitors including nivolumab, clinicians need to pay attention to the occurrence of skin disorders related to T-cell activation.